Outcome of Newborns with Tracheoesophageal Fistula: An Experience from a Rapidly Developing Country: Room for Improvement - Amal Al-Naimi; Sara G. Hamad; Abdalla Zarroug (Pulmonary Medicine)
Introduction/Purpose. Tracheoesophageal fistula (TEF) represents one of the most common congenital developmental malformations of the upper digestive tract. The optimal surgical management has several controversies, particularly in rapidly developing countries. Morbidity and mortality are highly variable between centers and are dependent on various factors. However, complex medical care has considerably improved, especially in developing countries. This study describes the experience of our center in patients with TEF with emphasis on the clinical characteristics, postoperative immediate and long-term respiratory and gastrointestinal complications, and the mortality rate of such cases which would allow us to compare our results with other regional pediatric tertiary centers. Methods. This is a retrospective review of the medical electronic charts of patients with TEF that were followed at Sidra Medicine in the state of Qatar. The review included the patients who were operated upon in the period of 2011-2021 but continued to follow at our institution in the period of 2018-2021. Demographic data, associated anomalies, preoperative, operative, and postoperative courses, and growth parameters were collected. Results. A total of 35 patients with TEF (24 males and 11 females) were collected. 49% were full term. We identified seven patients (20%) with isolated TEF, TEF with VACTERL association in 29% of our patients, other chromosomal anomalies in 17%, or associated with other anomalies (not related to VACTERL) in 34% of the patients. The majority of the patients (94%) were of type C-TEF (TEF with esophageal atresia–EA/TEF). All patients were operated except for one patient who died at 2 days of life due to cardiac complications. Median age at which surgery was performed was 2 days (range 1-270 days). Median follow-up was 32 months (range 7-115 months). Immediate postoperative complications were encountered in eleven patients (33%) and included anastomosis leak in 12%, air leak in 6%, sepsis in 6%, chylothorax in 3%, vocal cord palsy and fistula recurrence (combined) in 3%, and failure of TEF closure in 3% of the patients. Long-term respiratory complications were encountered in 43% of our patients. Long-term gastrointestinal complications included gastroesophageal reflux (GERD) in 63%, dysphagia in 31%, and anastomotic stricture in 34% of the patients. Growth was affected in around a quarter of the patients at 6 months after surgery and 22% at 12-month assessment postoperatively. While only five patients died at our institution, only one was directly related to failure of TEF closure and postoperative complications. Conclusion. This descriptive study reports the clinical outcome of TEF from a rapidly developing country. The distribution of the patients’ characteristics and postoperative complications was almost comparable to those from developed countries. This study would aid in addressing the prognostic factors and establishment of evidence-based management pathways of newborns with TEF to improve the clinical outcome in our center and other pediatric tertiary centers in developing countries.